The Development of Student Worksheet Integrated by Stem Approach in Plant Growth and Development Material to Train Bio-Entrepreneurship Skills - Mahmudi, Irkham; Susantini, Endang; Yakub, Pramita (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
The student worksheet based on Science, Technology, Engineering, and Mathematics / STEM approach was developed as an new teaching materials that can provide life experiences with the theme of biological entrepreneurship related to Wick hydroponics. This research aim was to produce student worksheets based on the STEM approach in plant growth and development material to train Bio-entrepreneurship skills in terms of theoretical and empirical feasibility. The development research used the 4D model started from define, design, develop, and disseminate. The research parameters measured from theoretical feasibility based on product validity, while empirical feasibility based on the results of the worksheet implementatiton in a small group of the 12th-grade student based on the level of Fry graph readability and the questionnaire responses. The results of the worksheet development on theoretical feasibility got a validity score of 3.65 with a very valid category. Empirical feasibility results based on the readability test at the 12th level, indicated that the information in the student worksheet was easily understood by 12th-grade students and got 95% of positive responses. This worksheet occupied the theoretical and empirical feasibility aspects so it was able to be used as an alternative teaching material developed using the STEM approach to trained students' Bio-entrepreneurship skills. Keywords: Student’s worksheet, Bio-entrepreneurship, plant growth and development, hydroponic Wick.